THE FOUNDATIONS OF STATE RESPONSIBILITY IN INTERNATIONAL LAW: AN IN-DEPTH ANALYSIS OF KEY PRINCIPLES AND NORMS - Shavkat Shukhrat Ugli, Nurilloev (Antis Publisher, 2024)
Objective: This article aims to explore the foundational principles and norms governing the responsibility of states in international law, with a focus on the legal frameworks outlined by the International Law Commission’s Articles on State Responsibility. It seeks to deepen the understanding of state accountability and its implications for international relations. Method: The study utilizes a comprehensive review of case law, scholarly interpretations, and legal frameworks to examine key concepts such as internationally wrongful acts, state liability, reparations, and compensation mechanisms. The research also considers the interplay between state sovereignty and international obligations. Results: The analysis reveals the challenges states face in adhering to their international legal commitments, particularly regarding the protection of human rights and the resolution of international disputes. It also highlights the complexities in balancing state sovereignty with legal accountability. Novelty: This article contributes a deeper understanding of state responsibility within the broader context of international relations, emphasizing the need for legal accountability in fostering stability and justice in the international community. It provides a nuanced perspective on how state responsibility operates in contemporary international law.